Impoliteness in EFL Complaints: Exploring its Intentions and Motivating Factors - Wijayanto, Agus; Hikmat, Mauly Halwat; Prasetyarini, Aryati (Bina Nusantara University, 2018)
The present study investigated intentions and motivating factors of using impoliteness in interlanguage complaints by EFL learners. Empirical data were elicited by means of oral discourse completion tasks and questionnaires from 42 Indonesian learners of English. Post-structured interviews were conducted to obtain the intentions and reasons of deploying impoliteness in the complaints. The results reveal that impoliteness is triggered by three general motivating factors; speaker-related factors, target person-related factors, and contextual factors. A number of intentions of deploying impoliteness are found, and they suggest that impoliteness is a means to an end rather than an end itself.